Urban renewal: at whose cost? - Patkar, Medha; Singh, Simpreet (2007)
Maharashtgra's draft housing policy seems to cater more to the builder lobby than the poor. In order to ensure shelter for al, the provisions of the Urban Land Ceiling and Regulation Act must be strictly implemented, basti sabhas on the lines of Gram Sabhas must be set up and poor localities should be treated not as encroachments but as service guilds. - Reproduced.
Keywords: Housing - India - Maharashtra; Urban renewal - India - Maharashtra; Urban renewal